Repeated peripheral administration of lipidized prolactin-releasing peptide analog induces c-fos and FosB expression in neurons of dorsomedial hypothalamic nucleus in male C57 mice - Pirník, Zdenko; Kolesárová, Mária; Železná, Blanka; Maletínská, Lenka (Neurochemistry international, 2018)
Previous studies indicate that hypothalamic prolactin-releasing peptide (PrRP), signaling via GPR10 and neuropeptide FF2 receptor, is involved in energy homeostasis, stress responses, and cardiovascular regulation. Energy homeostasis depends on the balance between food intake regulation and energy expenditure, in which the hypothalamus plays a key role. The lipidization of PrRP31 with palmitoyl acid allows it to produce its anorexigenic effect after repeated peripheral administration and to reduce body weight and improve metabolic parameters in diet-induced obese (DIO) mice. The aim of this study was to reveal the transient and long-lasting changes in neuronal activity via c-Fos and FosB immunohistochemistry in brain nuclei related to food intake regulation and energy homeostasis during the first days of treatment with a newly designed lipidized analog of PrRP31 (palm11-PrRP31) with promising antiobesity effects. The data revealed that the anorexigenic effect of repeated application of palm11-PrRP31 was associated with delayed but gradually significantly reduced cumulative food intake in mice as well as with a significant reduction in their body weight. Moreover, while the repeated application of palm11-PrRP31 was associated with a significant reduction in acute cell activity in the paraventricular hypothalamic nucleus (PVN) and nucleus of the solitary tract (NTS) compare to its acute treatment, both acute and long-lasting cell activity in the dorsomedial hypothalamic nucleus (DMN) were increased. The data indicate that DMN neurons might be tonically activated after repeated administration of lipidized PrRP analogs that may be associated with the process of long-term adaptation to modified energy homeostasis.
Keywords: energetický metabolismus; Hypothalamus; Male; c-Fos; FosB; Obesity; Lipidization; přijímání potravy; Dorsomedial hypothalamic nucleus; obezita; Dorsomedial Hypothalamic Nucleus; mužské pohlaví; Eating; neurony; Prolactin-Releasing Hormone; Body Weight; nucleus dorsomedialis hypothalami; lipidy; Animals; Prolactin-releasing peptide; Energy Metabolism; zvířata; Neurons; myši inbrední C57BL; hormon uvolňující prolaktin; Mice, Inbred C57BL; protoonkogenní proteiny c-fos; hypothalamus; Lipids; Mice; tělesná hmotnost; Proto-Oncogene Proteins c-fos